2020
DOI: 10.1111/camh.12415
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Practice: A randomised controlled feasibility trial of Behavioural Activation as a treatment for young people with depression

Abstract: Background: Behavioural Activation (BA) treatment effectively reduces symptoms of depression in adults and is more cost-effective than more complex therapies. Two recent systematic reviews of BA for depression in young people highlighted the need for more studies in this area. Methods: In order to evaluate the acceptability of BA treatment for adolescents with depression and the feasibility of conducting a trial of this intervention in Child and Adolescent Mental Health Services (CAMHS), 22 patients from acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Outcomes after therapy from the second study are in line with published RCTs of psychological therapies (Goodyer et al, 2008(Goodyer et al, , 2017. Other researchers using BA in specialist CAMHS have found similar results (Gudmundsen et al, 2016;Kitchen, Tiffin, Lewis, Gega, & Ekers, 2020;Pass, Lejuez, & Reynolds, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Outcomes after therapy from the second study are in line with published RCTs of psychological therapies (Goodyer et al, 2008(Goodyer et al, , 2017. Other researchers using BA in specialist CAMHS have found similar results (Gudmundsen et al, 2016;Kitchen, Tiffin, Lewis, Gega, & Ekers, 2020;Pass, Lejuez, & Reynolds, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Psychological treatments are considered to be one of the main treatment options for youth depression and meta-analyses have shown that these treatments are indeed effective, although the effects are modest, [ 7 ] and smaller than those in adults, especially in younger children [ 8 ]. Although most studies have focused on cognitive behaviour therapy (CBT) and to a smaller extent interpersonal therapy (IPT), several other types of therapy have also been examined in randomised controlled trials, including behavioural activation [ 9 ], problem-solving therapy [ 10 ] and family therapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the BUDDY RCT's design, quantitative methods and results has been published elsewhere (Kitchen et al, 2021 ). In brief, all study participants (young people) were asked to complete standardised questionnaires at three‐months post‐randomisation, and all those in the BA study arm ( n = 11) were invited to a qualitative interview.…”
Section: Methodsmentioning
confidence: 99%